Upper extremity 3‐dimensional reachable workspace assessment in amyotrophic lateral sclerosis by Kinect sensor. Issue 2 (29th December 2015) - Oskarsson, Bjorn; Joyce, Nanette C.; De Bie, Evan; Nicorici, Alina; Bajcsy, Ruzena; Kurillo, Gregorij; Han, Jay J.
ABSTRACT: Introduction : Reachable workspace is a measure that provides clinically meaningful information regarding arm function. In this study, a Kinect sensor was used to determine the spectrum of 3‐dimensional reachable workspace encountered in a cross‐sectional cohort of individuals with amyotrophic lateral sclerosis (ALS). Methods : Bilateral 3D reachable workspace was recorded from 10 subjects with ALS and 17 healthy controls. The data were normalized by each individual's arm length to obtain a reachable workspace relative surface area (RSA). Concurrent validity was assessed by correlation with scoring on the ALS Functional Rating Score—revised (ALSFRSr). Results : The Kinect‐measured reachable workspace RSA differed significantly between the ALS and control subjects (0.579 ± 0.226 vs. 0.786 ± 0.069; P < 0.001). The RSA demonstrated correlation with ALSFRSr upper extremity items (Spearman correlation ρ = 0.569; P = 0.009). With worsening upper extremity function, as categorized by the ALSFRSr, the reachable workspace also decreased progressively. Conclusions : This study demonstrates the feasibility and potential of using a novel Kinect‐based reachable workspace outcome measure in ALS. Muscle Nerve 53: 234–241, 2016